From Screen to Speech: Exploring EFL Students’ Beliefs About the Role of Bimodal Subtitles in Speaking Practice - Muzammil, Lasim; Andy, Andy; Liskinasih, Ayu; Milliard, Mallaury (Educare : Jurnal Penelitian Pendidikan dan Pembelajaran, 2025)
This study explores English language learners’ perceptions of bimodal subtitles‒simultaneous audio and text in the same language‒as a tool for developing speaking skills. While previous research has predominantly focused on the benefits of subtitles for receptive skills such as listening and vocabulary acquisition, limited attention has been paid to their influence on productive skills like speaking. Adopting a qualitative approach, this study gathers learner insights (N=62) through structured surveys and open-ended responses to examine how subtitled audiovisual materials shape learners’ confidence, pronunciation accuracy, and fluency. Five open-ended questions were grouped into thirty-six thematic EFLs’ responses (N = 532). Findings reveal that learners perceive bimodal subtitles as beneficial in enhancing speech production by offering real-time lexical and phonological reinforcement. Participants also reported an increase in their confidence when practicing spoken English. These perceptions align with prior research on multimodal learning and suggest that bimodal subtitles can be an accessible and effective scaffolding tool in language instruction. The study advocates for greater integration of subtitled media in pedagogical design, particularly in online and self-directed learning environments.